PENGARUH DISKON TANGGAL KEMBAR DAN GRATIS ONGKOS KIRIM DI SHOPEE TERHADAP KEPUTUSAN PEMBELIAN IMPLUSIF MAHASISWA - Ospariadi, Amanda Salsabila; Nailah, Balqis; Ghassani, Fakhrunnisa Naura; Suciati, Kumala; Gusti Asyafa, Meilla; Eryani, Ririn (Universitas Bengkulu, 2026)
This study aims to analyze the effect of double date discounts and free shipping promotions on impulse buying behavior among university students. The research focuses on students of the Management Study Program at Universitas Bengkulu as respondents. The method used in this study is a quantitative approach with a survey technique through questionnaires distributed online. The sampling technique applied is purposive sampling, with data measured using a Likert scale. Data analysis was conducted using SPSS, including validity, reliability, t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results of this study indicate that double date discounts have a positive and significant effect on impulse buying, as evidenced by a t-value of 4.221 with a significance value of less than 0.001. Meanwhile, free shipping does not have a significant effect on impulse buying, with a t-value of 0.218 and a significance value of 0.828. However, simultaneously, double date discounts and free shipping have a significant effect on impulse buying, as shown by an F-value of 30.133 and a significance value of less than 0.001. The coefficient of determination (R²) shows that 43.3% of impulse buying behavior can be explained by these variables, while the remaining 56.7% is influenced by other factors outside this study. These findings suggest that time-limited promotional strategies, particularly double date discounts, are more effective in encouraging impulse buying behavior among consumers.